The Stylistic Study of the Film Jelita Sejuba and Its Application in Literature Learning - Apriliana, Indah; Al-Ma'ruf, Ali Imran (Raja Zulkarnain Education Foundation, 2025)
The purpose of this study is to analyze the stylistic elements in the film Jelita Sejuba and explore their application in a science classroom at the high school level. The method used is a qualitative approach with observation techniques, film scene recording, and literature study. Data analysis was conducted using heuristic and hermeneutic analysis models, as well as theoretical triangulation validity to ensure data validity. The research findings indicate that the film Jelita Sejuba has a strong narrative structure with the main themes of sacrifice and loyalty, a mixed plot that builds audience emotion, characters rich in cultural and religious values, and a setting that highlights the local identity of Natuna. Stylistic aspects in this film include poetic diction, sentence style with personification, climax and anticlimax, the use of figurative language such as metaphors and symbolism, and a discourse style that reflects code-switching and code-mixing between Indonesian, Natuna Malay, and Arabic. The conclusion of this study confirms that the film Jelita Sejuba is very effective for use as a literature teaching material in high school because it can improve students’ understanding of stylistic concepts contextually, train their literary analysis skills, and encourage appreciation for language and culture through audiovisual media that is close to their lives and relevant in modern literature education in schools.